2007
DOI: 10.2169/internalmedicine.46.0092
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome in HD Patients: Association with Body Composition, Nutritional Status, Inflammation and Serum Iron

Abstract: Objective Insulin resistance and metabolic syndrome (MeS) iron, TIBC, transferrin saturation (TSAT), ferritin, calcium, phosphorus, intact parathormone (i-PTH), TNF-alpha, IL-6 and high sensitivity C-reactive protein (hs-CRP)] were used. All parameters were evaluated by comparisons between two groups, with MeS (Group 2) and without it (Group 1). Logistical regression analysis was used to evaluate the correlation between measured variables and the presence of MeS in HD patients. Independent variables for Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
8
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 29 publications
5
8
0
2
Order By: Relevance
“…[1][2][3][4][5] In this study, the prevalence was 59.5%, which is consistent with high prevalence of MeS in general Iranian population (50.8%). 24 Relatively little is known about the precise causes of such a high prevalence.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…[1][2][3][4][5] In this study, the prevalence was 59.5%, which is consistent with high prevalence of MeS in general Iranian population (50.8%). 24 Relatively little is known about the precise causes of such a high prevalence.…”
Section: Discussionsupporting
confidence: 88%
“…[26][27][28] However, our results showed that low HDL-C (85.6%) is the most prevalent MeS element in these patients, followed by hypertension (71.1%), which is in agreement with recent investigation in Iranian general population. 24 Similar to previous studies, MeS was prevalent among diabetics and female, and HD patients had higher age, WC, BMI, SBP, DBP, FPG, HbA1c, TG, and lower HDL-C levels 3,[26][27][28][29][30][31][32][33] and are just beginning the dialysis process. 29 Serum level of hsCRP, a marker of systemic inflammation, was more strongly related with MeS than other inflammatory biomarkers in regard not only to the number of components but also to their clustering, in agreement with previous reports in general population.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations